Secondary Osteosarcoma in Paget Disease: A Rare Case Report - Putri, Felicia Ivana; Setiawati, Rosy (Syntax Literate, 2026)
Osteosarcoma is a malignant bone tumor, which can develop with the formation of immature bone or osteoid. It most commonly affects in children and adolescents, while its occurrence in elderly patients is relatively rare. In elderly patients, osteosarcoma can arise with paget’s disease, a condition characterized by abnormal bone remodeling. This report presents an unusual case of osteosarcoma in elderly patients highlighting the importance of radiological and biopsy evaluation in establishing the diagnosis. A 66-year-old man presented with a history of a lump on the right lower extremity, present for the past ten years and progressively enlarging over the last six months. patient experienced pain both at rest and during movement. There was no history of trauma, falls, comorbidities or family history that were associated with disease. Plain radiographs, MRI, and needle biopsy were performed. Imaging studies demonstrated bone destruction, periosteal reaction, soft tissue extension, and matrix ossification which are characteristic findings of osteosarcoma. Pathological examination identified a clusters and dispersed anaplastic cells with round-to-oval, pleomorphic, and hyperchromatic nuclei. Incidence of osteosarcoma in elderly patients is rare and show a poorer prognosis than do children and adolescent patients. In this age group, osteosarcoma often arises as a secondary malignancy. Conditions such as Paget’s disease or prior malignancies are known contributors. Several predisposing factors for adult-onset osteosarcoma have been identified, including underlying genetic syndromes, benign bone lesions, and a history of radiation therapy or chemotherapy. Early diagnosis in older individuals is important often challenging due to atypical presentations, often leading to misdiagnosis or delayed recognition. In elderly patients, bone tumors require careful diagnostic workup. Plain radiography play central role in initial evaluation, MRI delineates soft tissue involvement and metastatic spread, and histopathology confirms the diagnosis.